2020
DOI: 10.1109/access.2020.2996506
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Study on Smart Stent for Autonomous Post-Endovascular Aneurysm Repair Surveillance

Abstract: Endovascular aneurysm repair (EVAR) is an established and reliable surgical treatment of abdominal aortic aneurysm (AAA), where a covered stent is implanted to prevent blood flow in the aneurysm sac. Although current EVAR is an effective technique, it requires long-term monitoring for the post-operative complications (e.g., endoleak, stent occlusion), which usually requires expensive radiologic imaging techniques such as ultrasonography, computed tomography (CT), or magnetic resonance imaging (MRI). In this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 30 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Currently, stent technology has been utilized beyond its traditional purposes, such as the SMART stent (stent with flow or pressure sensors) 47 , 48 and stents with recording electrodes 49 . By adding sensors and electrodes, stents are empowered with more functions to serve as potential new or better treatment options for intractable diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, stent technology has been utilized beyond its traditional purposes, such as the SMART stent (stent with flow or pressure sensors) 47 , 48 and stents with recording electrodes 49 . By adding sensors and electrodes, stents are empowered with more functions to serve as potential new or better treatment options for intractable diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The smart stent can generate 0.23 mW of electrical power when exposed to ultrasonic stimulation, which can sufficiently operate low‐power wireless electronics. [ 237 ] In another study, GO was added to PVDF via laser sintering to enhance its piezoelectric effect. The results indicated that the PVDF/0.3GO scaffold presented the best electrical performance, and the proliferation of cells cultured on this scaffold can be effectively enhanced when exposed to ultrasound.…”
Section: Advanced Designs Of Implants With Charge‐transfer Monitoring or Regulating Abilitiesmentioning
confidence: 99%
“…Copyright 2014, Wiley-VCH. d) Reproduced with permission [237]. Copyright 2020, Institute of Electrical and Electronics Engineers Inc.…”
mentioning
confidence: 99%